(3TQM GdTeGFd ddJQePjs - (3edG eMeO GdMfajs; (3GdJQePj , CHh YjSi,J (B279 (3g` s ((3OQhjT eMeO Hf bGSe Hf Ydi GdgQhi s)
(3ChdgG (B:s
(3bGd TcQ Gddg SYjg (B: (3GdMeO ddg GdMeO gh GdKGfGA Ydi GdLejd GdENJjGQi ef fYeI Ch ZjQgG s
(3BNQgG (B:s
(3hbY GdaQGZ ef JCdja TQM GdTeGFd jhe GdKdGFGA GdSGOS ef LeGOi GdChd SfI SJ hYTQjf hJSYeGFg HYhf Gddg hMSf JhajbI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B75 - (3U(B201s
(3GdfSNI HgG MhGTs
(3HgG eTgG JbjjOGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJGQjNs